In vitro susceptibility of Sporothrix spp. to complexes coordinated with Co(II) and cobalt chloride hexahydrate - Tchana Martinez Brandolt; Gabriel Baracy Klafke; Daniela Fernandes Ramos; Priscila Cristina Bartolomeu Halicki; Juliano Rosa de Menezes Vicenti; Willian Alikuri Pereira; Vanice Rodrigues Poester; Karine Ortiz Sanchotene; Melissa Orzechowski Xavier (Universidade de São Paulo, 2022)
Abstract Sporothrix spp. are the major dimorphic fungus associated with a type of subcutaneous mycosis, sporotrichosis. The limitation of antifungal availability and the past reports of in vitro resistance of Sporothrix spp. clinical isolates makes it important to search for new compounds with antifungal activities. In this study, we therefore evaluate the in vitro activities of complexes coordinated with Co(II) and cobalt chloride hexahydrate against clinical isolates of Sporothrix spp. Broth microdilution test was performed as per M38-A2 from CLSI (2008) in duplicate for 31 clinical isolates of Sporothrix spp. (27 S. brasiliensis e 04 S. schenckii stricto sensu). The antifungal activities of the complexes coordinated with Co(II) and cobalt chloride hexahydrate were detected at a concentration range of 32-128 µg/mL for all isolates. None of the compounds demonstrated any cytotoxicity (to macrophage cells) at the concentration of 200 µg/mL. The activity against Sporothrix spp. recorded in this study instigate the continuity of experimental studies with Co(II) to search for the mechanisms of antifungal action as well as to evaluate its interaction with the commercial antifungal drugs.